(untitled) (Research, Society and Development, 2022)
Lentivirosis of small ruminants affect goats and sheep and have a wide geographical distribution, causing serious economic losses, mainly in dairy goats. The objective of this work was to carry out the epidemiological characterization of the lentiviruses of small ruminants in the Immediate Geographic Region of Monteiro, Paraíba, Northeastern Brazil. Stratified probabilistic sampling was carried out in two stages: in the first, rural properties were randomly selected, and in the second, animals were randomly selected within the selected properties. Epidemiological questionnaires were applied in order to obtain information about the absence or presence of some practices and conditions that act as possible factors associated with the occurrence of the investigated diseases. The serological diagnosis was made with the Agar Gel Immunodiffusion test (IDGA) using a commercial kit. A serological examination (IDGA) of a sample of 890 goats was performed, which revealed a seroprevalence of 10.56% (94/890) for infection by LVPR (I.C. 95%). In the study it was possible to observe that two municipalities (Monteiro and Zabelê) had a prevalence of LVPR positive above 30% and the other municipalities varied between 1.06% and 11.70%. There was a high occurrence of animals seropositive for LVPR in herds of dairy goats in the immediate region of Monteiro, state of Paraíba, Brazil. The presence of this disease can have direct negative impacts on milk production, which is the focus of the goat farming established in the region in question, generating economic losses.